2006
DOI: 10.1021/bm050963w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Weight and Ionic Strength on the Formation of Polyelectrolyte Complexes Based on Poly(methacrylic acid) and Chitosan

Abstract: Chitosan/poly(methacrylic acid) complexes, CS/PMAA, were prepared via dropwise addition of a solution of PMAA to a solution of chitosan in acetic acid 2 wt %. The increase in molecular weight of PMAA inhibited the formation of insoluble complexes, while the increase in ionic strength first favored the formation of the complex followed by inhibiting it at higher concentrations. These observations were related to a description of polyelectrolyte complexation that was strongly dependent on macromolecular dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 59 publications
(100 reference statements)
4
83
0
Order By: Relevance
“…This transformation is an evidence of the formation of chitosan nanoparticles with MAA. According to the mechanism proposed by Vasconcelos et al [12], the formation of nanoparticles occurs via inter and intra-molecular linkages between PMAA carboxyl groups and amino groups of chitosan during the polimerization of MAA. Figure 1 shows a transmission electron microscopy (TEM) image of the chitosan nanoparticles (CS-PMAA).…”
Section: Resultsmentioning
confidence: 99%
“…This transformation is an evidence of the formation of chitosan nanoparticles with MAA. According to the mechanism proposed by Vasconcelos et al [12], the formation of nanoparticles occurs via inter and intra-molecular linkages between PMAA carboxyl groups and amino groups of chitosan during the polimerization of MAA. Figure 1 shows a transmission electron microscopy (TEM) image of the chitosan nanoparticles (CS-PMAA).…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of PEC nanoparticles is quite simple and can be easily performed under mild conditions without the use of toxic organic reagents. It has been demonstrated that chitosan can form PEC nanoparticles with various polyanions such as hyaluronic acid, chondroitin sulfates, alginate, carboxymethyl cellulose, carrageenan, heparin, and poly(acrylic acid) [84][85][86]. Recently, chitosan has been investigated as the carrier of a hydrophilic 5-FU by forming PEC nanoparticles with polyaspartic acid sodium salt [87].…”
Section: Chitosan-based Polyelectrolyte Complex (Pec) Nanoparticlesmentioning
confidence: 99%
“…The potential of combining two or more desirable properties by tailoring the material opens up a vast array of new possibilities (Decher 1997;de Vasconcelos et al 2006). The use of polyelectrolyte complexes (PECs), or polyelectrolyte multilayers (PEMs) have received quite a lot of attention in the field of research (Philipp et al 1989;Dautzenberg 1997;Decher 1997;Dautzenberg and Karibyants 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The properties and behavior of PECs in suspension has previously been studied by measurements of turbidity, static light scattering, dynamic light scattering, polyelectrolyte titration, viscosity, surface charge analysis, FTIR spectroscopy, and electrophoretic mobility (Buchhammer et al 1995;Dautzenberg 1997;Dautzenberg and Karibyants 1999;Dragan and Cristea 2001;Kekkonen et al 2001;Hubbe et al 2005;de Vasconcelos et al 2006). It has been reported that the formation of PECs is sensitive towards the nature of the cationic polyelectrolyte .…”
Section: Introductionmentioning
confidence: 99%